(untitled) (Medico Legal Update, 2019)
Competency of the fresh graduate nursing school remain got complains from the user of nursing services, especially in the hospital. This study aimed to identify the dominant factor upon the clinical competency of student of Nursing School of Health Polytechnic of Jakarta I. The research design was quasy-experimental with t-test and linear regression. Sample were 72 students. Data were collected using questionaires, then analyzed using the paired sample t-test. Based on t-test result, there was a significant difference in clinical competencies between pre and post intervention of clinical coaching in the hospital. It could be concluded that student centered learning method is significant in increasing clinical competencies of students.